Kajian Adaptasi Sosial Psikologis Pada Ibu Setelah Melahirkan (Post Partum) Di Ruang Rawat Inap RSUD Kota Semarang - Cahyo, Kusyogo; Rimawati, Eti; Widagdo, Laksmono; Solikha, Dewi Amila (Jurnal Promosi Kesehatan Indonesia, 2008)
Background: Delivery process is a big moment in women’s life and will effect to their role’s change. Psychological burden of post partum is an emotional symptoms and feeling like downhearted, insomnia, physically tired and do not know what they do with the new role. Role pressure and role could influence women’s depression development after delivery. Toavoid the physically tired, emotional increased and psychological crisis, human should learn to face the problem effectively by adaptation mechanism or adjustment. Family, friend and parent have important role in social system of delivery’s mother. The aim of research is to examine the socio-psychological adaptation among delivery’s mothers in In-patient department RSUD Kota Semarang.Method: The research design is qualitative study by emic dimension approach. The informants are ten mothers who had delivered 2 days, 2 nurses, and ten people from family delivery’s mother. Data collecting was conducted by in-depth interview with interview guideline. Data analysis was done by content analysis.Result: Age, education, and social economic status influenced psychology and physiology of delivery mothers. Experiences and family support were being reinforcing factors for delivery mothers to adapt after delivery.Key words: adaptation, socio-psychology, delivery’s mother